2008
DOI: 10.1681/asn.2007070744
|View full text |Cite
|
Sign up to set email alerts
|

IL-6/IL-6R Axis Plays a Critical Role in Acute Kidney Injury

Abstract: The response to tissue injury involves the coordination of inflammatory and repair processes. IL-6 expression correlates with the onset and severity of acute kidney injury (AKI), but its contribution to pathogenesis remains unclear. This study established a critical role for IL-6 in both the inflammatory response and the resolution of AKI. IL-6 -deficient mice were resistant to HgCl 2 -induced AKI compared with wild-type mice. The accumulation of peritubular neutrophils was lower in IL-6 -deficient mice than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
281
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 327 publications
(297 citation statements)
references
References 51 publications
11
281
1
4
Order By: Relevance
“…Because aggravation was mediated by classic signaling, the effects were unlikely to be mediated by resident nonhematopoietic renal cells as these do not express the IL-6R. 43,55 Rather, aggravation of disease was more likely to be affected by leukocytes, which, except for hepatocytes, are the only cells known to express IL-6R on their surface. 56 In this regard, we wanted to study the role of macrophages because macrophages are known to be potent effectors of tissue injury in NTN 42 and IL-6 was postulated to downregulate macrophage activation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because aggravation was mediated by classic signaling, the effects were unlikely to be mediated by resident nonhematopoietic renal cells as these do not express the IL-6R. 43,55 Rather, aggravation of disease was more likely to be affected by leukocytes, which, except for hepatocytes, are the only cells known to express IL-6R on their surface. 56 In this regard, we wanted to study the role of macrophages because macrophages are known to be potent effectors of tissue injury in NTN 42 and IL-6 was postulated to downregulate macrophage activation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the anti-inflammatory role of IL-6 in NTN, a more recent study found protective effects of IL-6 trans-signaling in AKI. 43 Regarding the situation in humans, IL-6 secretion from PBMCs correlated with renal disease activity in lupus nephritis. 44 Urinary IL-6 has also been suggested as a marker for renal inflammation in different forms of GN.…”
mentioning
confidence: 99%
“…IL-6 is a major proinflammatory mediator well characterized in the orchestration of the inflammatory response following acute renal insult 4,5 and has been shown to be a superior marker in renal patients compared with other proinflammatory candidates, such as the systemic inflammatory marker C-reactive protein. [6][7][8][9] On the other hand, IL-10, while not as established in kidney injury, is appreciated to be a prototypical anti-inflammatory cytokine that carries out the critical function of modulating inflammation.…”
mentioning
confidence: 99%
“…12 STAT3 is also activated in renal tubule cells during AKI and plays a critical role in the response to injury. 13 Following AKI, SOCS3 levels are depressed, corresponding with increased STAT3 activity associated with the tubule repair process. 14 Both the loss and overexpression of SOCS3 have been associated with renal disease.…”
mentioning
confidence: 99%